Pembuktian Jual Beli Tanah di Bawah Tangan dalam Sengketa Perdata: Analisis Putusan PN Nabire No. 30/Pdt.G/2020/PN Nabire - Moulyta Elgi Trinanda; Muhammad Ivansyah Fadlillah S; Muhammad Valeska Ramadhan (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study discusses the position of private deeds as evidence in disputes over land rights transfers through a study of Nabire District Court Decision No. 30/Pdt.G/2020/PN Nabire. A normative-doctrinal approach was used to analyze the provisions of Article 1320 of the Civil Code, Article 164 of the HIR, Article 1866 of the Civil Code, Article 1874 of the Civil Code, and Article 37 of Government Regulation No. 24 of 1997, as well as relevant judicial practices. The results of the analysis show that private deeds obtain probative legitimacy if they are not contested and are combined with factual evidence, such as payment and delivery of the object, so that the judge can form a legal conviction to validate the transfer of rights. Court decisions serve as instruments of temporary administrative legalization without removing the formal obligations of the PPAT, affirming the flexibility of the civil evidence system. These findings emphasize the orientation towards material truth, legal protection for parties acting in good faith, and harmonization between material validity and formal legal certainty, while enriching the doctrine of substantial evidence in civil land disputes in Indonesia.